Net zero business models : winning in the global net zero economy - Montgomery, John B.; Van Clieaf, Mark (Ascent Audio, 2023)
Future-proof your business with net-zero emissions strategies that align with new economic realities In Net Zero Business Models: Winning in the Global Net Zero Economy, two accomplished business transformation thought leaders deliver a revolutionary new take on how to transition from business models that are contributing to worldwide climate disaster to net zero models consistent with long-term sustainability. In the book, you'll discover what net zero emissions means, how to implement net zero emission business models, what the overall transition to a net zero emissions economy looks like, and, ultimately, how civilization itself will transition to net zero. The authors offer new processes and tools for diagnosing current business models and designing a viable transition to net zero. They establish a universal language for conversations about decarbonizing the economy by synthesizing business model design terminology and new integrated measurement and reporting statistics. Listeners will also find: accessible and comprehensible presentations of net zero emissions concepts, business models, and economies; concrete strategies for transforming existing business models into net zero-compatible models; and frameworks for analyzing the consequences of conforming existing business models to a net zero emissions economy.